1995
DOI: 10.1042/bj3100197
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatic carbonic anhydrase in de novo lipogenesis

Abstract: The role of carbonic anhydrase in de novo lipid synthesis was examined by measuring [1-14C]acetate incorporation into total lipids, fatty acids and non-saponifiable lipids in freshly isolated rat hepatocytes. Two carbonic anhydrase inhibitors, trifluoromethylsulphonamide (TFMS) and ethoxozolamide (ETZ) decreased incorporation of 14C into total lipids. Both fatty acid and non-saponifiable lipid components of the total lipid were inhibited to approximately the same extent by 100 microM TFMS (29 +/- 0.3% and 35 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 29 publications
1
76
0
Order By: Relevance
“…A time-dependent decrease in carbonic anhydrase activity was reported in fish exposed to chlorpyrifos (35). Carbonic anhydrase in hepatocyte mitochondria plays a vital role in the regulation of ionic balance, which is required in metabolic reactions, production of ATP, and transport processes (102).…”
Section: Biochemical Evidence Of Op Hepatotoxicitymentioning
confidence: 99%
“…A time-dependent decrease in carbonic anhydrase activity was reported in fish exposed to chlorpyrifos (35). Carbonic anhydrase in hepatocyte mitochondria plays a vital role in the regulation of ionic balance, which is required in metabolic reactions, production of ATP, and transport processes (102).…”
Section: Biochemical Evidence Of Op Hepatotoxicitymentioning
confidence: 99%
“…Weakly acidic metabo!ites labelled with 14C were separated by ion-exchange chromatography on Dowex 1 chloride columns as described previously (Lynch et al, 1995). Chromatographic peaks were identified based on parallel column runs with radiolabelled standards and/or assays of the peak fractions by luminometric or fluorometric methods (Williamson and Corkey, 1969).…”
Section: Chromatographic Separation Of 14c-labelled Metabolitesmentioning
confidence: 99%
“…Values range from 13% (Lapidot and Gopher, 1994) to 5% (Shank et a!., 1993). Recent studies from this laboratory demonstrate that carbonic anhydrase inhibitors, such as ethoxyzo!amide, when added to hepatocytes (Lynch et a!., 1995), adipocytes (Hazen eta!., 1996), or astrocytes (Hazen eta!., 1997) lower flux through pyruvate carboxylase by limiting its access to bicarbonate (HCO 3~). As carbonic anhydrase inhibitors are sometimes used to treat epilepsy, it may be possible that these drugs are effective because they lower glutamate and g!utamine levels in brain by !owering flux through pyruvate carboxy!ase in astrocytes.…”
mentioning
confidence: 99%
“…In addition, Herbert and Coulson (1983) demonstrated that de novo fatty acid synthesis (measured by [ 14 C]acetate incorporation into total lipid) in liver of American chameleons (Anolis carolinensis) was inhibited by CA-specific inhibitors (ethoxyzolamide and acetazolamide). CA was suggested to play a role in de novo lipogenesis in hepatocytes by increasing the rate of CO 2 hydration to bicarbonate for ACCase (Dodgson et al, 1984), and Lynch et al (1995) reported a reduction of [ 14 C]acetate incorporation into total lipid in rat hepatocytes incubated with CA inhibitors trifluoromethylsulphonamide and ethoxyzolamide. Together, these results support the notion that CA assists in providing HCO 3 ÏȘ for lipid biosynthesis in animal systems.…”
mentioning
confidence: 99%